The absolute lactate levels versus clearance for prognostication of post‐cardiotomy patients on veno‐arterial ECMO - Mohamed Laimoud; Patricia Machado; Michelle Gretchen Lo; Mary Jane Maghirang; Emad Hakami; Rehan Qureshi (ESC Heart Failure)
Abstract Aims Veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO) is a life‐saving procedure for supporting patients with cardiogenic shock after cardiac surgery. This work aimed to analyse the impact of changes in blood lactate levels on the survival of patients on post‐cardiotomy ECMO (PC‐ECMO) and whether lactate clearance (LC) performs better than absolute lactate levels. Methods and Results We retrospectively analysed the data of adult patients who received PC‐ECMO at our centre between 2016 and 2022. The primary outcome was the in‐hospital mortality rate. Arterial lactate levels were measured at ECMO initiation, peak and 12 and 24 h after VA‐ECMO support. LC was calculated at 12 and 24 h. Out of 2368 patients who received cardiac surgeries, 152 (median age, 48 years; 57.9% of them were men) received PC‐ECMO. Of them, 48 (31.6%) survived and were discharged, while 104 (68.4%) died during the index hospitalization. Non‐survivors had higher frequencies of atrial fibrillation (41.35% vs. 12.5%, P < 0.001), chronic kidney disease (26.9% vs. 6.3%, P = 0.004), prolonged cardiopulmonary bypass (237 vs. 192 min, P = 0.016) and aortic cross‐clamping times (160 vs. 124 min, P = 0.04) than survivors. Non‐survivors had a significantly higher median Sequential Organ Failure Assessment (SOFA) score at ECMO initiation (13.5 vs. 9, P < 0.001) and a lower median Survival After Veno‐arterial ECMO (SAVE) score (−3 vs. 3, P < 0.001) with higher SAVE classes (P < 0.001) than survivors. After 12 h of VA‐ECMO support, the blood lactate level was negatively correlated with LC in survivors (r = −0.755, P < 0.001) and non‐survivors (r = −0.601, P < 0.001). After 24 h, the same negative correlation was identified between survivors (r = −0.764, P < 0.001) and non‐survivors (r = −0.847, P < 0.001). Blood lactate levels measured at 12 h to determine hospital mortality [>8.2 mmol/L, area under the receiver operating characteristic curve (AUROC): 0.868] and 24 h (>2.6 mmol/L, AUROC: 0.896) had the best performance, followed by LC‐T12 (<21.94%, AUROC: 0.807), LC‐T24 (<40.3%, AUROC: 0.839) and peak blood lactate (>14.35 mmol/L, AUROC: 0.828). The initial pre‐ECMO blood lactate (>6.25 mmol/L, AUROC: 0.731) had an acceptable ability to discriminate mortality but was less than the following measurements and clearance. Kaplan–Meier curves demonstrated that LC of <21.94% at T12 h and <40.3% at T24 h was associated with decreased survival (log‐rank P < 0.001). Cox proportional hazards regression analysis for mortality revealed that LC of <21.94% at T12 h had an adjusted hazard ratio (HR) of 2.73 [95% confidence interval (CI): 1.64–5.762, P < 0.001] and LC of <40.3% at T24 h had an adjusted HR of 1.98 (95% CI: 1.46–4.173, P < 0.001). The predictors of hospital mortality after PC‐ECMO were the lactate level at 12 h [odds ratio (OR): 1.67, 95% CI: 1.121–2.181, P = 0.001], initial SOFA score (OR: 1.593, 95% CI: 1.15–2.73, P < 0.001), initial blood lactate (OR: 1.21, 95% CI: 1.016–1.721, P = 0.032) and atrial fibrillation (OR: 6.17, 95% CI: 2.37–57.214, P = 0.003). Bivariate models using lactate levels and clearance at the same points revealed that blood lactate levels performed better than the clearance percentage. Conclusions Serial measurements of arterial blood lactate and LC help in obtaining early prognostic guidance in adult patients supported by VA‐ECMO after cardiac surgery. Absolute lactate levels, compared with LC at the same time points, demonstrated better performance in differentiating mortality.